Quality of life after VATS lung resection and SABR for early-stage non-small cell lung cancer: A longitudinal study. (December 2021) - Pompili, Cecilia; Rogers, Zoe; Absolom, Kate; Holch, Patricia; Clayton, Beverly; Callister, Matthew; Robson, Johnathan; Brunelli, Alessandro; Franks, Kevin; Velikova, Galina
Highlights: Quality of life data through validated EORTC questionnaires is feasible and well accepted by patients submitted to treatment of early-stage NSCLC. Quality of life over the first year after early-stage NSCLC treatments shows different trends. Functional scores are reported stable after Stereotactic Ablative Body Radiotherapy. After VATS resection, patients reported a temporary worsening in QoL with subsequent improvement at twelve months. Abstract: Introduction: Video-assisted thoracoscopic (VATS) lung resection is the recommended curative treatment for early-stage non-small cell lung cancer (NSCLC). Patients considered at high surgical risk, are treated with stereotactic ablative body radiotherapy (SABR) as a lower morbidity alternative. This study aims to investigate the impact of SABR and VATS resection on patients' quality of life (QoL) over the first year after treatment. Methods: A prospective longitudinal observational study recruiting early-stage NSCLC patients from a single UK centre. QoL was assessed with EORTC QLQ-C30 and Lung Cancer Module LC13 at baseline, 6 weeks and 3, 6 and 12 months post-treatment. Results: From 01.03.2017 till 01.03.2018, 244/281 patients (87%) consented to participate, 225 (95 SABR and 130 VATS) were included in the analysis. SABR patients had significantly worse baseline QoL scores than VATS patients, even after adjusting for preoperative clinical factors (C-30 Global Health mean: SABR = 53.8, VATS = 71.2; Physical Functioning mean: SABR = 57, VATS = 82.2; Fatigue mean: SABR = 43.5, VATS = 23.7; C30 Dyspnea mean: SABR = 49.5, VATS = 26.2). During the 12 months post SABR treatment patients' QoL scores remained stable. In the VATS group, there was a deterioration 6-weeks after treatment in Role, Physical, Social Functions, Global Health, Fatigue, C30/LC13 Dyspnoea, Pain, Appetite loss, Constipation, LC13 Pain in Chest and Arms. The scores improved by 12 months without reaching the preoperative values. Conclusions: Although QoL outcomes for SABR and VATS are not comparable due to different medical selection criteria, the QoL impact of the two treatments during the first year showed different trends which will inform patients and clinicians during decision-making discussions.